2017
DOI: 10.1007/s11010-017-3081-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase CK2 sensitizes non-small cell lung cancer cells to cisplatin via upregulation of PML

Abstract: Non-small cell lung carcinoma (NSCLC), a malignancy of lungs, is very aggressive and usually ends up with a dismal prognosis. Cisplatin (CDDP)-based systemic chemotherapy is the main pharmaceutical approach for treating NSCLC, but its effect is discounted by some hitherto unknown reasons. Thus, this study is dedicated to improving the efficacy of CDDP. Our results show that combining use of CDDP with CK2 siRNA or inhibitor is more efficient in suppressing cancer cell growth and promoting apoptosis than use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We have previously shown in prostate cancer that CK2 inhibition has a negative impact on mitochondrial health through decreased membrane potential and Ca 2+ flux [ 27 , 46 ]. CK2 has significant influence on numerous DNA repair and other pathways activated by radiation and cisplatin [ 27 , 47 , 48 , 49 ]; loss of CK2 improves sensitivity to cisplatin or radiation in numerous cancers, including head and neck cancer [ 42 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. CX-4945 blocks DNA repair after cisplatin or gemcitabine treatment [ 51 , 63 ], and next generation platinum Pt(IV) prodrugs conjugated with CX-4945 have shown efficacy in other cancer types [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown in prostate cancer that CK2 inhibition has a negative impact on mitochondrial health through decreased membrane potential and Ca 2+ flux [ 27 , 46 ]. CK2 has significant influence on numerous DNA repair and other pathways activated by radiation and cisplatin [ 27 , 47 , 48 , 49 ]; loss of CK2 improves sensitivity to cisplatin or radiation in numerous cancers, including head and neck cancer [ 42 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. CX-4945 blocks DNA repair after cisplatin or gemcitabine treatment [ 51 , 63 ], and next generation platinum Pt(IV) prodrugs conjugated with CX-4945 have shown efficacy in other cancer types [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear scaffold protein promyelocytic leukemia gene (PML) has a dual role in cancer: it can act as the downstream target of oncogenic RAS and it can promote tumorigenesis (31). PML is a pro-apoptosis gene that can be indirectly suppressed by cisplatin-based systemic chemotherapy in nonsmall cell lung carcinoma (32). Additionally, it is suggested that it has a potential role in immune-modulatory approaches for treating lung cancer with aberrant PML degradation (33).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of targeting CK2 in combination with Cisplatin-based compounds is also supported by the observation of an increased CK2 expression in response to these drugs: this was reported by Yang et al [76], who observed down-regulation of the tumor suppressor PML in cisplatin-treated lung cancer cells, as a consequence of CK2α overexpression.…”
Section: Main Textmentioning
confidence: 81%